2001
DOI: 10.1038/sj.ijo.0801546
|View full text |Cite
|
Sign up to set email alerts
|

The effect of addition of modified guar gum to a low-energy semisolid meal on appetite and body weight loss

Abstract: OBJECTIVE:To investigate the effect of addition of modi®ed guar gum (GG) to a low-energy semisolid meal on appetite and body weight (BW) loss. SUBJECTS: Twenty eight mainly overweight male volunteers (age, 19 ± 56 y; body mass index, 29 AE 2 kg m À2 ; BW, 89.4 AE 9.2 kg). DESIGN: Baseline of one week with self-selected diet. Three treatments of 2 weeks with a low-energy diet divided over three times a day, consisting of a semisolid meal with (SSM ) or without GG (SSM) or a solid meal (SM) with the same energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…The subjects were recruited by advertisements in local newspapers, in which we asked for moderately obese male subjects who wanted to participate in a study on the effects of different low-energy diets on appetite, food intake and body weight. The subjects were a subsample of the study mentioned before that is described in Kovacs et al (2001). Selection for this study with a more intensive protocol took place according to health criteria (fasting blood glucose < 6.2 mmol=l; blood pressure < 95 mmHg (diastolic) and < 160 mmHg (systolic), no diabetes, no cardiovascular diseases, and no medical treatment) and body weight criteria (body mass index: 25 -30 kg=m 2 ).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects were recruited by advertisements in local newspapers, in which we asked for moderately obese male subjects who wanted to participate in a study on the effects of different low-energy diets on appetite, food intake and body weight. The subjects were a subsample of the study mentioned before that is described in Kovacs et al (2001). Selection for this study with a more intensive protocol took place according to health criteria (fasting blood glucose < 6.2 mmol=l; blood pressure < 95 mmHg (diastolic) and < 160 mmHg (systolic), no diabetes, no cardiovascular diseases, and no medical treatment) and body weight criteria (body mass index: 25 -30 kg=m 2 ).…”
Section: Subjectsmentioning
confidence: 99%
“…The experimental design consisted of three treatments, each consisting of a 2 week low-energy diet and a subsequent time-blinded test, separated by a 4 week washout period (Figure 1; Kovacs et al, 2001).…”
Section: Experimental Designmentioning
confidence: 99%
“…Astrup et al (1990) and Quaade et al (1990) reported lower hunger scores when the energy-restricted diet was supplemented with 30 g of fibre per day, whereas Kovacs et al (2001) and Kovacs et al (2002) observed no such effect.…”
Section: Dietary Fibrementioning
confidence: 99%
“…Based on available evidence on bowel function, the Panel considered dietary fibre intakes of 25 g/day to be adequate for normal laxation in adults on an habitual diet (EFSA NDA Panel, 2010a). Dietary fibre doses of around 7-30 g/day with total diet replacements for weight control have been reported Quaade et al, 1990;Kovacs et al, 2001;Kovacs et al, 2002). Often the amount is individually determined.…”
Section: Dietary Fibrementioning
confidence: 99%
See 1 more Smart Citation